Push Factors and Pull Factors for Domestic Tourists Visiting Melasti Badung Beach Tourism Attraction - Taora, Nayahana Hobori; Agustini, Ni Putu Oka; Wiarti, Luh Yusni (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
he purpose of this study was to determine the driving factors and pulling factors for domestic tourists to visit Melasti Beach. This study used purposive sampling of 115 respondents. The sample in this study were domestic tourists aged 17 years and over who had visited Melasti Beach at least since 2021. The data analysis techniques used were validity testing, reliability testing, and Exploratory Factor Analysis. The results showed that the driving factors remained the same as the initial factors and 2 new pulling factors were formed. The most dominant driving factor was the enhancement of kinship relationships factor with an eigenvalue of 4.890 and a total variance of 34.930. The most dominant pulling factor was the attraction and facilities factor with an eigenvalue of 3.551 and a total variance of 50.727.